Rectal pyogenic granulomas: an uncommon cause of gastrointestinal bleeding - Devrim, Tuba; Utku, Özlem Gül; Oğuz, Dilek (Turkish Journal of Gastroenterology, 2018)
Abstract Cite this article as: Devrim T, Utku ÖG, Oğuz D. Rectal pyogenic granulomas: an uncommon cause of gastrointestinal bleeding. Turk J Gastroenterol 2018; 29: 122-3.